Domestic price distortions and agricultural income in developing countries - Bautista, Romeo M. (Elsevier, 1986)
The static effects on agricultural crop production and income arising from the correction of three common policy biases in developing countries - the underpricing of food, agricultural export taxation, and currency overvaluation - are examined analytically and empirically (using Philippine data) based on a model of the agricultural sector with the food-export crop tradeoff in production as a key component. The findings argue for a careful examination of the relative efficiencies of different liberalization policy instruments in advancing specific development objectives in cases where, possibly for socio-political reasons, not all price distortions in interrelated markets can be corrected.